The ancient art of persuasion across genres and topics - Dēmētriou, Kyriakos N.,; Papaioannou, Sophia,; Serafim, Andreas, (International Studies in the History of Rhetoric;, 2020)
"Persuasion has long been one of the major fields of interest for researchers across a wide range of disciplines. The present volume aims to establish a framework to enhance the understanding of the features, manifestations and purposes of persuasion across all Greek and Roman genres and in various institutional contexts. The volume considers the impact of persuasion techniques upon the audience, and how precisely they help speakers/authors achieve their goals. It also explores the convergences and divergences in deploying persuasion strategies in different genres, such as historiography and oratory, and in a variety of topics. This discussion contributes towards a more complete understanding of persuasion that will help to advance knowledge of decision-making processes in varied institutional contexts in antiquity".